Radio frequency interference (RFI) mapping for radio astronomy in Peninsular Malaysia / Roslan Umar - Umar, Roslan (2014)

(untitled)
Radio astronomy observations are increasingly contaminated by human-made Radio Frequency Interferences (RFI). If these interferences are continuously present, they will be a major problem for radio astronomers in their observations. The purpose of this study is to create a radio interference intensity distribution map of Peninsular Malaysia using the RFI mapping technique. The Geographical Information System (GIS) was employed as a tool to carry out the mapping technique. A systematic procedure of decision analyses has been proposed by Drobne and Lisec, namely Multi Criteria Decision Analysis (MCDA), in order to process complex and various amounts of data obtained from different sources, and it offers many benefits, such as cost-effective, and efficient and rapid management. The proper decision-making process for selection of local RFI sites requires collection of information of various parameters. The factors that affect the selection process were decided and taken into account. In this study, the parameters involved are: the population density, the presence of telecommunication transmitters (e.g: mobile phone, radio and television), road networks, the rain effect and contour shielding. In this study, we found that the most suitable value for population density was below 150ppl km